Association of COMT polymorphism and academic achievement among female undergraduate students / Norsuhaila Rosmimi Rosli ...[et al.] - Rosli, Norsuhaila Rosmimi; Anuar, Tengku Shahrul; Adenan, Mohd Ilham; Mohd Janor, Roziah; Ahmad, Rohana; Teh, Lay Kek; Salleh, Mohd Zaki; Abu Bakar, Sahol Hamid; James, Richard Johari (Faculty of Applied Sciences, 2021)
Academic achievement may be influenced by catechol-O-methyltransferase (COMT) polymorphism. A common functional polymorphism of COMT, the rs4680 is consistently being involved in the modulation of dopaminergic pathway and prefrontal cortex function which may predominantly affect cognitive functions. A total of 197 female participants were recruited in this study. The score of student's grade point average (GPA) from the latest previous semester was used as the measurement of academic achievement. The COMT polymorphism was genotyped using tetra primer allele specific polymerase chain reaction. The findings indicated that there were 8 (4.1 %), 72 (36.5 %), and 117 (59.4 %) participants harbouring Met/Met, Met/Val, and Val/Val genotype for COMT polymorphism respectively. All the genotype distributions of COMT polymorphism were consistent with Hardy-Weinberg equilibrium (χ2 = 0.495, p > 0.05). The one-way analysis of variance (ANOVA) result demonstrated that participants bearing Met/Met genotype had a better achievement in GPA as compared to the other COMT genotypes (p = 0.001). These findings support evidence that the affective role of COMT polymorphism might overwhelm cognitive abilities in measures of academic achievement like GPA.